Long‐Term Evaluation of Changes in Operative Technique and Hardware‐Related Complications With Deep Brain Stimulation. Issue 8 (5th August 2015) - Falowski, Steven M.; Ooi, Yinn Cher; Bakay, Roy A.E.
Abstract : Background: Deep brain stimulation is the most frequent neurosurgical procedure for movement disorders. Objective: While this elective procedure carries a low‐risk profile, it is not free of complications. As a new procedure, the pattern of complications changed with experience and modification of surgical technique and equipment. Methods: This review analyzes the most common hardware‐related complications that may occur and techniques to avoid them. It is a retrospective review of 432 patients undergoing 1077 procedures over a 14‐year period by one surgeon with emphasis on the analysis of surgical technique and the changes over time. Comparisons were made pre and postimplementation of different surgical techniques over different time periods. The epochs relate to the learning curve, new equipment, and new techniques. Results: Overall lead revision was observed at 5.7%, extension revision at 3.2%, infection rate at 1.2%, infarct without intracerebral hemorrhage at 0.8%, and intracerebral hemorrhage at 2.5% with a permanent deficit of 0.2%. An analysis and change in surgical technique which involved isolating the lead from the skin surface at both the cranial and retro‐auricular incision also demonstrated a substantial decrease in lead fracture rate and infection rate. There was no mortality. Conclusion: This large series of patients and long‐term follow‐up demonstrates that risks are very low in comparison with other neurosurgical procedures, but DBS is still an elective procedure that necessitates extensive care and precision. In a rapidly evolving field, attention to surgical technique is imperative and will keep rates of complications at a minimum.